Keterbukaan Informasi Publik Dalam Upaya Mewujudkan Good Governance pada Pemerinah Kabupaten Tegal - Fatullatifah, Menik; Ngabiyanto, Ngabiyanto; Munandar, Moh Aris (Unnes Political Science Journal, 2017)
This research is motivated by the existence of freedom information which became one of the human rights that contained in the 1945 Constitution. The Public Information Openness existence is supported by the presence of UU KIP as legal security of information opennes in public agency. The existence of Public Information Openness (KIP) became one of the efforts to achieving Good Governance towards governmental that free from corruption. Tegal Regency Government have some significant corruption cases records from the Year 2011-2015. Based on this cases, It needs to do a research in the KIP of Tegal Regency Government. Based on the background, the research problem formulation, namely,  How is the Public Information Openness in  Tegal Regency Government and What kind of driving  factors and inhibiting factors of Public Information Openness in Tegal Regency Government. This research uses a qualitative approach method. The subject of of this research is the Vice Regent, Regional Secretariat of Public Relations, PPID, and Tegal Citizens. The results this research show the Public Information Openness of Tegal Regency Government seen from the governments efforts in providing information services, access to the documents, the existence financial transparency, and the existence of public aspirations shelters. Whereas the openness is not optimal due to the information services has not been supported by the local television media as the media which is more populist and have not establish a press center for media. The supporting factors of openness is the commitment of the leaders and the existence of legal protection. While the inhibiting factors of openness are the lack of socialization about KIP Act, lack of public knowledge about KIP, and the misuse of information. In order for public information openness on Tegal Regency Government run optimally, It is necessary to develop the information and communication media, such as local television media, It needs comprehension and public awareness about the right of public information with socialization and publication of the citizens right for information and mechanisms obtaining information, and it need for public participation in the use of Public Information Opennes to supervise the government.